Review of Isolation Methods, Chemical Composition and Biological Activities of Curcuma aeruginosa Roxb Rizhome - Suharsanti, Ririn; Astuti, Puji; Yuniarti, Nunung; Wahyuono, Subagus (Faculty of Pharmacy, University of Benin, 2022)
Curcuma aeruginosa Roxb rhizome is known as temu ireng or temu hitam in Indonesia and has been widely used as a traditional medicine in Asia. There have been many studies to reveal the chemical content of Curcuma aeruginosa Roxb rhizome, some of which are influenced by the isolation methods. Several separation and purification methods were identified including essential oil distillation, extraction and chromatography. This study aims to describe, analyze and discuss the isolation methods of chemicals compounds Curcuma aeruginosa Roxb rhizome, how the techniques influence the types and composition of the components and to examine which compounds have potential biological activities. The method used for review articles is explored several databases such as PubMed and Scopus to identify and download abstracts, original articles, and research papers related to extraction followed by fractionation, isolation, and chemical components of Curcuma aeruginosa Roxb. The inclusion criteria used were the article year between 2010-2020, the part used for the study was the rhizome, there was a discussion of isolation process, components that have been isolated and their biological activity. The exclusion criteria used were articles whose samples were only up to the extraction stage and articles whose methods were unclear. Chemical compounds of Curcuma aeruginosa Roxb rhizome can be carried out in various ways, including steam distillation, water distillation, extraction, fractionation to isolation by chromatography, especially column chromatography with elution gradient. Germacron is the most isolated and has several biological activities. © 2022 Suharsanti et al.